The effect of R&D, technology commercialization capabilities and innovation performance - Kim, Seo Kyun; Lee, Bong Gyou; Park, Beom Soo; Oh, Kyoung Seok (Technological and Economic Development of Economy, 2011)
This paper investigates the relationship between R&D capabilities (learning, R&D and external networking), technology commercialization (manufacturing and marketing), and innovation performance (product competitiveness) among SMEs in IT-related businesses. The study focuses on 254 Korean IT SMEs that were either recipients of government R&D grants or their indirect beneficiaries during the two-year period between 2005 and 2007. The major findings of this study are as follows: First, unlike what has been suggested by previous studies, R&D intensity was not the only factor influencing the innovation performance of firms; learning and external networking also had a significant influence on innovation. The research implication of this finding is that the measurement of firms’ performance should not be solely based on the intensity of R&D expenditures, but a broader set of factors including learning and external networking capabilities. Second, the technology commercialization capabilities of firms played the role of a mediator in the relationship between R&D and innovation performance. Within the innovation cycle of input (R&D capabilities), process (technology commercialization capabilities) and output (innovation performance), we found that R&D seldom influenced performance in a direct fashion, but its influence was most often mediated by technology commercialization capabilities. The practical implication of this finding for companies is that in order to improve performance, they must avoid narrowly focusing on R&D, but must invest also in capabilities to commercialize technologies resulting from R&D. Third, when direct and indirect beneficiaries of public R&D funding are compared together, the explanatory power of the relationship between R&D capabilities, technology commercialization capabilities and innovation performance was stronger among the latter than the former.Article in English.Mokslinių tyrimų ir eksperimentinės plėtros bei technologijų komercializavimo galimybės įtaka inovacijų efektyvumuiSantrauka. Straipsnyje tiriamas ryšys tarp mokslinių tyrimų ir eksperimentinės plėtros (MT ir EP), technologijų komercializavimo (gamybos ir rinkodaros) bei inovacijų efektyvumo (produkto konkurencingumo) smulkiose ir vidutinėse informacinių technologijų (IT) įmonėse. Buvo tiriamos 254 Korėjos smulkios ir vidutinės IT įmonės, kurios buvo valstybės paramos gavėjos arba gavo netiesioginę paramą 2005–2007 m. Pagrindinės tyrimo išvados yra šios: mokslinių tyrimų ir eksperimentinės plėtros mastas nėra vienintelis veiksnys, darantis įtaką inovacijų efektyvumui įmonėse; mokymas ir išorinis komunikavimas taip pat daro didelę įtaką inovacijoms. Taigi įmonių veiklos vertinimas neturėtų būti grindžiamas tik mokslinių tyrimų ir eksperimentinės plėtros intensyvumu, bet ir kitais veiksniais, kaip mokymo ir išorinio komunikavimo galimybės. Įmonės turėtų investuoti į galimybes komercializuoti technologijas, sukurtas mokslinių tyrimų ir eksperimentinės plėtros metu.Reikšminiai žodžiai: technologijų komercializavimas, inovacijų efektyvumas, moksliniai tyrimai ir eksperimentinė veikla.First published online 18 Jan 2012